Manufacturing Practice : Introduction To Welding Shop And Gas & Arc Welding-1 - Sankara Rao, Dr. Lakkoju (Main Workshop, Indian Institute of Technology (BHU), Varanasi, 2016)
This video describes the introduction to manual metal arc welding and oxy acetylene welding process.
Keywords: Welding Shop; Gas & Arc; oxy acetylene